2018
DOI: 10.1038/s41598-018-33834-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel glycyrrhizin metabolite as a causal candidate compound for pseudoaldosteronism

Abstract: Pseudoaldosteronism is a common adverse effect associated with traditional Japanese Kampo medicines. The pathogenesis is mainly caused by 3-monoglucuronyl glycyrrhetinic acid (3MGA), one of the metabolites of glycyrrhizin (GL) contained in licorice. We developed an anti-3MGA monoclonal antibody (MAb) and an ELISA system to easily detect 3MGA in the plasma and urine of the patients. However, we found that some metabolites of GL cross-reacted with this MAb. Mrp2-deficient Eisai Hyperbilirubinemia rats (EHBRs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…In terms of safety, we found that OCG capsules showed a satisfactory safety profile for patients with chronic eczema, as no patients experienced serious adverse events during our study. Nevertheless, long-term use of OCG may increase the risk of some adverse events, such as pseudoaldosteronism [25,26]. Known effects of pseudoaldosteronism were observed in our study, as three (3.2%) patients developed lower extremity edema, one (1.1%) experienced hypokalemia, and two (2.1%) had new-onset high blood pressure.…”
Section: Discussionsupporting
confidence: 49%
“…In terms of safety, we found that OCG capsules showed a satisfactory safety profile for patients with chronic eczema, as no patients experienced serious adverse events during our study. Nevertheless, long-term use of OCG may increase the risk of some adverse events, such as pseudoaldosteronism [25,26]. Known effects of pseudoaldosteronism were observed in our study, as three (3.2%) patients developed lower extremity edema, one (1.1%) experienced hypokalemia, and two (2.1%) had new-onset high blood pressure.…”
Section: Discussionsupporting
confidence: 49%
“…We found that most of 2 and 3 in plasma was bound to albumin, suggesting that these two compounds would not be eliminated into the urine via glomerular filtration, but rather via tubular secretion. As 1 had a high binding ratio to albumin and was a substrate for OAT1 and 3 18 and 2 and 3 share a high binding ratio to albumin, these compounds can be transported into the cells actively via OAT1 and 3, and eliminated into the urine by tubular secretion. As GA also has a high binding ratio to albumin but is not a substrate for OATs, GA was not detected in the urine in either SD rats or EHBRs.…”
Section: Discussionmentioning
confidence: 99%
“…From these results, we developed an anti-3MGA-monoclonal antibody (mAb) and an enzyme-linked immunosorbent assay (ELISA) to easily detect 3MGA in the blood or urine of patients who took licorice, in order to prevent pseudoaldosteronism by predicting the individual body constitution causing this condition without using expensive instruments such as LC-MS/MS 18 . However, 3MGA detected by ELISA in the plasma and urine of EHBRs treated with GA was observed at concentrations much higher than those analyzed using LC-MS/MS, suggesting that the anti-3MGA-mAb cross-reacted with other metabolites of GA 18 . Eastern blot analysis using anti-3MGA-mAb with the urine from EHBRs treated with GA revealed another metabolite, 22 α -hydroxy-18 β -glycyrrhetyl-3- O -sulfate-30-glucuronide ( 1 , Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations